Factors Associated With Older Adults' Enrollment in Balance Classes to Prevent Falls: Case-Control Study. (August 2020) - Currie, Dustin W.; Thoreson, Sallie R.; Clark, Lauren; Goss, Cynthia W.; Marosits, Mark J.; DiGuiseppi, Carolyn G.
Balance training decreases fall risk among older adults, but few participate in such training. We examined the association of exposure to social marketing to promote balance classes, personal characteristics and other factors, with older adults' balance class participation. Adults aged ⩾60 years were eligible for this case-control study if they attended any church enrolled in a trial testing the effect of social marketing on balance class participation. Cases attended balance classes during the study period; controls were randomly sampled congregants who did not join a class. Cases were more likely to attend churches that received the social marketing program, and were older, more often female, and more frequently experienced "near falls" than controls. Participation was also associated with increasing age of the church's leader and rural church attendance. Programs to promote balance classes may need to be tailored to target some risk groups, including men and urban and suburban congregants.